Physiological and biochemical changes after a programmed kumite in male Shotokan karate practitioners - Petrov, L.; Penov, R.; Kolimechkov, S.; Alexandrova, A. (Archives of Budo Science of Martial Arts and Extreme Sports, 2018)
Background & Study Aim In recent years, physiological testing in karate has been focused on the specific characteristics of this sport. Some of the tests in karate have their intensity close to competitive bouts, but do not simulate competitive conditions, while other tests simulate a competitive workload, but their intensity is not pre-determined. The aim of this study was to create a model of programmed kumite, which includes the techniques most often used in competitions, and which has a pre-determined intensity close to that employed under competitive conditions.